Pendekatan Kontekstual dalam Pendidikan Seni Budaya Berbasis Kearifan Lokal di SMA Negeri 18 Surabaya - Rizky Arinka Dwi Cahya; Warih Handayaningrum (Universitas Negeri Surabaya, 2026)
This article aims to describe how SMA Negeri 18 Surabaya integrates local culture into arts and culture learning, to explain the synergy between teachers and students in its implementation, and to analyze the learning outcomes as an effort to preserve local culture. The research employed a descriptive qualitative approach. Data were collected from March to April 2026 through classroom observations in classes X-7 and XI-3, in-depth interviews with the vice principal for curriculum affairs, two arts teachers, one regional language teacher, and two students, as well as documentation of lesson plans and school documents. Data were analyzed through reduction, display, and conclusion drawing using source and technique triangulation. The findings show that local culture is integrated through Remo dance material, ceramic crafts, karawitan, digital learning media, learning facilities, and P5 exhibitions themed on local wisdom. Teacher–student synergy becomes stronger when learning moves toward practice, demonstration, and project work, although cultural meaning is not yet evenly internalized. Learning outcomes are reflected in visual artworks, dance performances, and the emergence of students’ initial appreciation of local culture. The main challenges include the dominance of popular culture, limited practice time, and the incomplete integration between arts education and regional language learning. The study concludes that arts and culture learning at SMA Negeri 18 Surabaya has become a medium for preserving local culture, although stronger reflection and interdisciplinary integration are still needed.